ANALISIS BELANJA LANGSUNG BERDASARKAN PERATURAN WALIKOTA PALU NOMOR 19 TAHUN 2014 DI KECAMATAN PADA PEMERINTAH DAERAH KOTA PALU - Safitri, Friningsih (Katalogis, 2016)
One of essencesin the law number 23 in 2014 states that The Camat (The District Chief) has partial authority to implement the government affairs in his territory. Delegation of authority in Palu City is regulated in the mayor’s rule number 19 in 2014. This research objects to explore the extent of direct expenditure to be implemented in district in Palu City and applies a qualitative approach. The study covers all district offices in Palu and selects 7 key informants from Palu Regional Secretary, DPPKAD of Palu, BAPPEDA and Penanaman Modal (invesment agency) both in district and municipally areas. The result of the study shows that : 1) delegation of authority is not effective; 2) the allocation budget is not in accordance with budget proposed by the district based on rule no. 19, 2014; 3) budget allocation is limited by budget constraints relating to local revenues.